Characterization of various modified asphalts using force ductility test with "8" shaped mold and straight mold. (21st November 2022) - Zhang, Jiakang; He, Anzheng; Xie, Bin; Wang, Jiaxin; Yan, Chuanqi
Highlight: Force ductility tests were carried out using "8" shaped mold and straight mold. Three failure types (brittle fracture, flow failure, and ductile fracture) were identified and summarized. Three stages (elastic, yield, and slender neck) were identified in the force–deformation curve. True stress was introduced to highlight the toughening effect of elastic modified asphalts. The "8″ shape mold exhibits better discrimination ability and less variability than the straight mold. Abstract: To explore a suitable mold for the force ductility test and propose a new index to better characterize low-temperature properties of modified asphalt, plain asphalt (PG 58–16, PG 52–22), styrene–butadienestyrene (SBS) modified asphalt (4.2 %, 7.5 %), low-density polyethylene (LDPE) modified asphalt (3 %, 8 %) and crumb rubber modified asphalt (20 %) were characterized using the force ductility test with "8" shaped mold and straight mold, respectively. The difference between their failure types and force–deformation curve evolution stages was analyzed. True stress was calculated to highlight the toughening effect of elastic polymer modifiers. Results demonstrate that three failure types (brittle fracture, flow failure, and ductile fracture) and three deformation stages (elastic, yield, and slender neck stage) can be observed and summarized for the force ductility test. The ductile failure and slender neck deformation stage is only observed for elastic-modified asphalts, which highlights the elastic polymer's toughening effect. "8" shaped mold appears to be a better choice than straight mold due to its better discrimination ability and less variability. The calculated true fracture stress has a very strong correlation (R 2 > 0.95) with deformation energy, which shows a good discrimination between modified asphalts.